Audio Visual-based DOMAR Media to Improve Second-Grade Elementary School Students' Listening Skills - Tharisya Dwi Rahmatiar; Sukardi (Jurnal Pendidikan dan Pengajaran, 2023)
Limited media and classical teaching patterns used in Indonesian language learning. This results in less effective student learning processes in building language skills. Audio-visual-based DOMAR (Picture Fairy Tales) media was developed based on this background. This research aims to analyze the development process, feasibility, and effectiveness of media in improving the listening skills of class II students. The method in this research is the development method or Research and Development (R&D). The subjects in this research were second-grade elementary school students. The development model in this research is the ADDIE model with the following stages: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data collection consists of observation, interviews, and documentation. Data analysis uses paired sample tests. The results of this development show that the media validation questionnaire is 90% and the material validation questionnaire is 89%, which is included in the very feasible category. In assessing student responses, the average percentage was 89%, and teacher responses were 88% with very good criteria. So, the media developed is very suitable for use in learning Indonesian.